Diversifikasi Produk Tempe Melalui Bioteknologi Konvensional Inovasi Tempe Sagu dan Kewirausahaan di SMA IT YARSI Mataram - Puspitasari Ningthias , Dyah; Sakaroni , Rubiyatna; Listantia, Nora; Hijriati , Sartika (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Conventional tempeh production faces several challenges, including high soybean prices and a short shelf life. Therefore, innovation through the diversification of raw materials is needed as a solution based on conventional biotechnology. This activity aimed to enhance the skills of students at SMA IT YARSI Mataram in producing sago tempeh as an innovative, economically valuable, and competitive product. The method employed consisted of an educational workshop combined with hands-on practice, including a pre-test, education on conventional biotechnology, principles of sanitation and hygiene, demonstration, sago tempeh production practice, and a post-test. Data were analyzed using SPSS. The results showed a significant increase in participants’ knowledge of food safety (p = 0.037), improved technical skills in sago tempeh production, and the emergence of entrepreneurial interest among students. The implications of this activity suggest that practice-based workshops can serve as an effective means to instill entrepreneurial spirit and local food technology skills in the younger generation.